The Effects of Substance Abuse Following Personal Injury: Five Case Studies from a Medico-Legal Context - James A Athanasou (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2015)
The focus of this paper is on the vocational, educational and psychosocial consequences of dependence or pathological overuse of a drug in relation to a personal injury. The clinically significant impairment or distress accompanying addiction [1], together with the neurobiological features of drug reward [2] are already welldocumented. There has been a concern for medication use and its effects in relation to injury [3]. For instance, dependence on pharmacological control of pain has been mentioned in relation to burn injuries [4] The substance abuse of patients with compensable injuries, however, has been documented but only sporadically since the early 1990s [5] and almost exclusively in relation to spinal cord injury or traumatic brain injury. Indeed, Bombardier and Turner [6] used traumatic brain injury and spinal cord injury as explicit "examples of disabling conditions in which alcohol- or drug-related problems play a significant role" (p. 241) whereas musculoskeletal injuries are 33 times more frequent than head injury in an Australian context [7].